OTIMIZAÇÃO DA SECAGEM DE ALFAVACA (Ocimum gratissimum L.) VISANDO REDUÇÃO DO TEMPO DE SECAGEM E O MÁXIMO RENDIMENTO DE ÓLEO ESSENCIAL. - Santos, Germano Rodrigues Furtado dos (2021)
Ocimum gratissimum, known as Alfavaca, is widely used in folk medicine due to its antiseptic effects, and in the treatment of digestive and respiratory diseases. Due to its therapeutic potential, it was included in the National List of Medicinal Plants of Interest in the Brazilian health system. Medicinal plants used as raw material for the pharmaceutical industry, or commercialization in the form of teas, must be stored until processing and use. In this context, drying is a suitable alternative for preserving the post-harvest quality of these products. However, this process has the inconvenience of the possibility of destruction or volatilization of thermo-sensitive components, such as essential oil, influencing the quality of the product. An alternative to minimize this risk is the use of intermittent drying, in which the drying period is interrupted, enabling an increase in effective diffusivity, and positively impacting the process. Therefore, this work aimed to optimize the drying process to minimize the drying time and maximize the yield of Ocimum gratissimum L. oil. A central rotational composite design was used to determine the conditions of the treatments, establishing the levels of the variables drying time, intermittence time, and time for intermittence insertion. The mathematical model that best described the drying kinetics was the Midilli model, with the best fit. The relationship between the effective diffusivity coefficient values and the drying air temperature was described by the Arrhenius equation. Afterward, the essential oil yield values for each treatment were obtained. Then, the desirability function was used to define the optimal process conditions to minimize the processing time and maximize the essential oil yield. It was found that the optimum point occurs at drying air temperature at 58.4 °C, rest time equal to 16.11 min, and insertion time equal to 14.92 min. In this condition, the estimated value for drying time is 88.86 min and for yield is 0.4833.